Sustainable Development Goals in Arabic Language Textbook for Sixth Grade in the Hashemite Kingdom of Jordan and the United Arab Emirates: A Comparative Analytical Study - Ababneh, Eman Abed Alfattah (Dirasat: Educational Sciences, 2024)
Objectives: To identify the Sustainable Development Goals (SDGs) included in the sixth-grade Arabic language textbooks in Jordan and the United Arab Emirates. Methods: A qualitative approach was employed using a comparative descriptive method. The researcher developed a tool for analysis. Results: The Jordanian textbook featured 508 instances of SDG-related content, while the Emirati textbook had 982 instances. The results showed that SDG 4, "Quality Education," and SDG 16, "Promoting Social Cohesion for Participatory Societies," were the most prominent in both the Jordanian and Emirati textbooks. In the Jordanian textbook, SDG 16 ranked first in frequency with 126 mentions (24.8%), while in the Emirati textbook, it ranked second with 166 mentions (16.9%). Conversely, SDG 4 ranked first in the Emirati textbook with 206 mentions (20.9%) and second in the Jordanian textbook with 69 mentions (13.5%). SDG 11, "Making Cities Sustainable," was absent from the Jordanian textbook, while SDG 14, "Sustainable Use of Marine and Terrestrial Resources," was not mentioned in the Emirati textbook. Conclusion: The Jordanian and Emirati Arabic language textbooks emphasize certain Sustainable Development Goals while neglecting others. The study recommends a more balanced inclusion of SDGs in both textbooks.